PSXII-15 Evaluation of later timing of fixed-time artificial insemination for beef cows when using sex-sorted semen following the 7 & 7 Synch protocol. (8th October 2021) - Andersen, Carson M; Smith, Emily G; VanWye, Genna M; Thomas, Jordan M
Abstract: An experiment was designed to evaluate later timing of fixed-time artificial insemination (FTAI) with sex-sorted semen among postpartum beef cows following the 7 & 7 Synch protocol, with the hypothesis that later timing would result in increased pregnancy rates (P/AI) among cows that expressed estrus prior to FTAI. Beef cows (n = 414) were blocked based on age and days postpartum (DPP) and randomly assigned to receive FTAI at 66 or 72 h after administration of prostaglandin F2α (PG). Estrus was synchronized using the 7 & 7 Synch protocol, which consists of administration of PG (500 μg cloprostenol) and insertion of an intravaginal progesterone-releasing insert (CIDR; 1.38 g progesterone) on Day 0, gonadotropin-releasing hormone (GnRH; 100 μg gonadorelin) on Day 7, and PG coincident with CIDR removal on Day 14. Estrus detection aids (Estrotect TM ) were applied to all cows on Day 14, and activation status was recorded at fixed-time artificial insemination (FTAI) on Day 17. All cows that expressed estrus prior to FTAI received sex-sorted semen (4 × 10 6 cells per unit; SexedULTRA 4M TM ). The proportion of cows expressing estrus prior to FTAI did not differ between treatments at this power of test [66 h: 71% (146/205); 72 h: 76% (158/209)]. Additionally, P/AI of estrous cows inseminated with sex-sorted semen did not differ between treatments [66 h: 44% (90/205); 72 h: 39% (82/209)]. In conclusion, later timing of FTAI following the 7 & 7 Synch protocol failed to improve P/AI of estrous cows inseminated with sex-sorted semen.